miRNAs as Novel Biomarkers of Chronic Kidney Injury in Anabolic-Androgenic Steroid Users: An Experimental Study - Sessa, Francesco; Salerno, Monica; Bertozzi, Giuseppe; Cipolloni, Luigi; Messina, Giovanni; Aromatario, Mariarosaria; Polo, Lorenzo; Turillazzi, Emanuela; Pomara, Cristoforo (Frontiers in Pharmacology, 2020)
miRNAs are a family of 20–22 non-coding nucleotides that control gene expression by inhibiting the translation of their target messenger RNAs (mRNAs). Two models have been proposed to elucidate the mechanism of action: they act either hindering mRNA translation or enhancing mRNA degradation. Anabolic-Androgenic Steroids (AASs) represent a class of drugs used to treat several diseases. In the last few years, AASs have frequently been used for aesthetic purposes, indeed, they are also called form part of the larger group called image- and performance-enhancing drugs (IPEDs). Long-term AAS use can lead to serious health consequences. In this regard, the present study aimed to analyze the role of several microRNAs (miRNAs) in renal damage after AAS use, to better understand the underlying mechanisms. For this purpose, two miRNAs (miR-21 and miR-205) were tested in two groups: AAS group (seven males, mean age 33.28 ± 4.68 years; mean body mass index (BMI) 27.04 ± 1.07), and chronic kidney disease (CKD) group (seven males, mean age 66.2 ± 5.4 years; mean BMI 24.75 ± 1.35). Finally, the same miRNAs were tested in the “Control” group (seven males, mean age 44.85 ± 5.75 years; mean BMI 26.5 ± 1.88). Kolmogorov-Smirnov Test was used to determine the normality of data distribution. All variables were normally distributed. Student’s t-test was used for comparisons between two groups. Analyzing the results of the present study, the two tested miRNAs (miR-21 and miR-205) were significantly higher in the CKD group compared to the AAS group, with mir-21 being much more expressed than miR-205. This study represents a pilot study to define if these expression patterns could be studied in other biological samples (plasma, urine) in subjects with different kidney injury linked to chronic kidney diseases and AAS use, to identify reliable biomarkers that could be applied in clinical and forensic diagnostics, as well as a target for toxicological investigations or therapeutic treatments.